Pendaftaran Tanah Dalam Sertipikasi Hak Menurut Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah - HAIRAN (Fakultas Hukum Universitas Mulawarman, 2008)
The development of Indonesian land registration has some complexities. In termof history, the agrarian consideration develops well in ancient time. Before theNetherlands based Agrarian Act (Agrarisch Wet), land registration has been conductedby the government of Netherlands, known as Kadasteral or kadaster. Since gaining itsindependence, Indonesia considers the new registration by establishing Indonesiangenuine law products after the prevailing of Indonesian Republic Act No.5 of 1960 onAgrarian Principles. The government follows it by validating the GovernmentRegulation No.10 of 1961 on Land Registration. During a longer period, since 1961 to1997, and following the development of land registration, in 1997, the prevailing ofGovernment Regulation No.24 of 1997 on Land Registration remains as the perfectionof previous regulation.Key words: pendaftaran tanah (land registration), sertipikat (certificate), hak (right)